Analysis and Design of Student Guidance Information System through Software Development Life Cycle (SDLC) and Waterfall Model - Henoch Juli Christanto; Yerik Afrianto Singgalen (Universitas Bina Darma, 2023)
Universities play an essential role in encouraging digital literacy as a form of support to accelerate digital transformation in Indonesia. One of the strategic steps to support the acceleration of digital transformation is to carry out organizational change in the academic scope. One of the innovative ideas to facilitate the thesis registration process, selection of supervisors, and thesis consultation is the existence of an integrated and accountable control system. This research proposes an idea to analyze and design the Information System for Thesis Consultation Process known as SIBIMA using the Software Life Cycle Development (SDLC) method according to the Waterfall model. SIBIMA is intended to support services in the education sector by adjusting the context of the values of the Atma Jaya Catholic University of Indonesia, namely Kristiani, Unggul, Peduli, and Profesional. Thus, students, lecturers, and academic staff complement each other in improving the quality of education. The case study of application design is adjusted to the registration process, selection of supervisors, and thesis consultation at the Head of Tourism Department, Faculty of Business Administration and Communication Sciences, Atma Jaya Catholic University of Indonesia.